Implementation models and frameworks used to guide community-based physical activity programs for children: a scoping review - Emma Ostermeier; Shauna M. Burke; Jason Gilliland; Patricia Tucker (BMC, 2023)
Abstract Background The implementation of community-based programs is key to effective, sustainable initiatives that can support population-level changes in children's physical activity. The purpose of this scoping review was to explore the implementation models and frameworks used to develop (process models), explore (determinant frameworks), and/or evaluate (evaluation frameworks) community-based physical activity programs for children. Also, the foundational components of the implementation models and frameworks and practical application in real-world settings were described. Methods The methodological framework developed by Arksey and O'Malley (2005) and the updated recommendations from Levac, Colquhoun and O'Brien (2010) were used to search, identify, and summarize applicable studies. This review also met the requirements in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Scoping Reviews Checklist (PRISMA-ScR). A detailed search of six databases and three academic journals was conducted. Information about the article, the program, and the implementation model/framework were extracted and summarized. Results The search retrieved 42,202 articles, of which 27 met the inclusion criteria. Eleven process models, one determinant framework, and two evaluation frameworks were identified. Nineteen components were developed from the models and frameworks. Tailoring, situational analysis, and element identification were common components among the identified models and frameworks. Conclusions Since the execution of interventions is vital for creating successful health-promoting initiatives, researchers and program developers should consider using implementation models and frameworks to guide their community-based physical activity programs. Further research examining the application of new and existing implementation models and frameworks in developing, exploring, and evaluating community-level programs is warranted.